2013
DOI: 10.5897/ajb2013.13241
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic components, antioxidant activity, and mineral analysis of Capparis spinosa L

Abstract: In addition to being consumed as food, caper (Capparis spinosa L.) fruits are also used in folk medicine to treat inflammatory disorders, such as rheumatism. C. spinosa L. is rich in phenolic compounds, making it increasingly popular because of its components' potential benefits to human health. We analyzed a number of individual phenolic compounds and investigated in vitro biological activities of C. spinosa L. Sixteen phenolic constituents were identified using reverse phase-high performance liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 31 publications
(28 reference statements)
0
21
1
Order By: Relevance
“…However, we preferred to use a different and more effective solvent system. As the results of one study (17) revealed that the ethyl acetate: methanol: distilled water (60:30:10) system is a well-known system to extract antioxidant compounds; the percent of yield of Rumex obtusifolius seeds hydroalcoholic extract was 5.3 gram.…”
Section: Extraction Yield Total Polyphenolics and Flavonoid Contentsmentioning
confidence: 99%
“…However, we preferred to use a different and more effective solvent system. As the results of one study (17) revealed that the ethyl acetate: methanol: distilled water (60:30:10) system is a well-known system to extract antioxidant compounds; the percent of yield of Rumex obtusifolius seeds hydroalcoholic extract was 5.3 gram.…”
Section: Extraction Yield Total Polyphenolics and Flavonoid Contentsmentioning
confidence: 99%
“…This difference in the amount of total phenolic extracted compounds can be due to differences in environmental conditions of plant growth and experimental conditions (30). Arrar et al (31) reported that total phenolic compounds extracted from Caper root with methanol solvent and distilled water, by maceration method, were 9.2 mg/g and 15.5 mg/g, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…So that the higher the phenolic compounds, the higher the antioxidant activity and the less IC 50 . Rezzan et al (30) investigated phenolic compounds, antioxidant activity, and mineral analysis of Capparis Spinosa using ultrasonic bath extraction. They reported that the mean plant compounds had an inhibitory concentration of 0.32 mg/mL, which showed less antioxidant activity than that of the present study (30).…”
Section: Discussionmentioning
confidence: 99%
“…The total polyphenolic and flavonoid contents of the caper extracts from the five above-mentioned areas of Pantelleria Island (Allaith, 2016), and than Turkish cappers containing 37 mg GAE/100 g DM (Aliyazicioglu, Eyupoglu, Sahin, Yildiz, & Baltas, 2013). Also data regarding TFC indicated that the relative amount of the secondary metabolites is affected by the geographic areas and the different genotypes; in fact, capers from Scauri had a higher significant content in flavonoids than other areas, and than capers from Kingdom of Bahrain (Aliyazicioglu et al, 2013). Overall, TPC and TFC of Pantelleria caper extracts are higher than other common food stuff such as parsley, red kale, bell pepper, tomato, and squash (Chandra et al, 2014).…”
Section: Nutraceutical Properties Of Caper Extractsmentioning
confidence: 99%